Fiscal Impacts of Climate Anomalies - Francesco Jacopo Pintus; Jan P.A.M. Jacobs; Elmer Sterken (CESifo GmbH, 2024)
The negative effects of climate change on output and productivity have been well documented in recent years. However, its impact on public finances has received little attention. This paper attempts to fill this gap by analysing the impact of climate anomalies on fiscal variables in a macroeconometric framework that also takes into account economic activity. We exploit natural weather variations to construct temperature and precipitation shocks in a panel of 14 European countries and the United States. Impulse response functions from a structural Bayesian Panel VAR show that adverse climate shocks are contractionary and significantly increase public debt and deficits over a business cycle horizon. However, the inflationary impact and the persistence of temperature and precipitation shocks are quite different. The negative fiscal and economic consequences of temperature anomalies are remarkably stronger for warmer, climate-vulnerable and highly indebted countries. Further analysis suggests that the main transmission mechanisms of the reported fiscal impacts are significantly lower tax revenues combined with an increase in government spending on public subsidies.
Keywords: C32; E62; H62; Q54; 330; public debt; climate change; panel data; structural Bayesian VAR